Social projection planing as a way of creation of the future in the information society - Клешня, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
Cultural and philosophical analysis of social engineering in the context of cultural and civilization expansion process in information age are analyzed.